Empowering Public Relations’ Practitioners to Achieve Sustainable Development Goals - Kyoosh, Khalaf Kareem (ALBAHITH ALALAMI, 2023)
The research aims to outline a governmental and societal communicative vision grounded in the principles of sustainable development within Iraqi governmental institutions. This is achieved by public relations practitioners incorporating these concepts and enhancing public awareness of them. Iraqi governmental institutions cannot deviate from the international pattern and societal mood that encompass the goals of sustainable development. The growing international and local interest in environmental issues has influenced governmental stances and actions towards the public. The research’s main problem revolves around addressing a pivotal question: What are the levels of empowerment of public relations practitioners in achieving sustainable development goals within governmental institutions? The primary objective of the research is to unveil the extent to which public relations practitioners perceive the required levels of sustainable development both domestically and externally and in their professional lives. Public relations and media practitioners are keen on educating about the significance and legitimacy of sustainable development. Their performance and success in fulfilling this role depend on their conviction and their ability to understand and adopt behaviors that align with sustainable development objectives. The study made several conclusions, most notably that public relations practitioners are aware of what is expected of an individual at home, externally, and at work. Additionally, the youth demographic is the most informed about sustainable development concepts and principles, making them more positive in their interactions with the requirements and behaviors of these principles, whether at home, in the community, or at work.